Meetings and resolutions adopted by the British trade union and labour movement, and the International Federation of Trade Unions and the Labour and Socialist International : summaries - Labour Party (Great Britain) ; International Federation of Trade Unions ; Labour and Socialist International
1937; 1938 017b-0033-004 292/946/17b/40(iv)